Patients’ Experience With Evaluation by Both a Musculoskeletal Physician and Physical Therapist in the Same Digital Visit: Survey Study - Mary I O'Connor; Carolyn Chudy; Kaitlyn C Peters; Megan Ribaudo; Carrie McCulloch; Jared Aguilar; Trista Taylor; Ryan A Grant (JMIR Formative Research)
Abstract BackgroundPatients undergoing evaluation for musculoskeletal concerns are often seen by a physician and physical therapist in the in-person setting in a sequential manner. This process typically delays the onset of nonoperative care, inclusive of physical therapy, and creates the risk of inadequate clinical collaboration between physician and physical therapist. To address these issues, we designed a novel initial patient evaluation to a group visit in which both a specialty-trained musculoskeletal physician and physical therapist simultaneously evaluate a patient together in the digital encounter. ObjectiveThe aim of the study is to gain insights from patients on their experience with this innovative digital simultaneous musculoskeletal medical doctor and physical therapist (MD+PT) visit format for the initial evaluation of musculoskeletal concerns. MethodsAn electronic 7-question survey was sent to 750 patients who completed an MD+PT visit asking them to comment on prior musculoskeletal evaluations and their experience with the MD+PT format. ResultsIn total, 195 (26%) patients responded to the survey with the frequent body regions of diagnosis being lumbar spine (n=65), knee (n=32), shoulder (n=21), cervical spine (n=20), hip (n=14), and hand (n=11). Most patients had prior musculoskeletal experience with a physician or nurse practitioner (171/195, 87.7%) or physical therapist (148/195, 75.9%) with nearly all such encounters in the in-person setting (161/171,94.2% for physician or nurse practitioner and 144/148, 97.3% for physical therapy). Only 3.1% (6/193) of patients reported seeing both a physician and physical therapist during the same in-person visit. Patients rated the simultaneous MD+PT visit very favorably: this type of digital evaluation saved them time (179/192, 93.2%) and permitted them to promptly start their treatment plan (174/192, 90.6%). Overall, 87.5% (168/192) rated the MD+PT visit as enjoyable, and 92.2% (177/192) responded that it increased their confidence with understanding their medical condition and how to start treating it. ConclusionsOur early experience with the evaluation of patients with musculoskeletal conditions by both a specialty-trained musculoskeletal physician and physical therapist simultaneously in the same digital visit resulted in patients reporting a very positive experience with high satisfaction, engagement, and confidence in understanding their diagnosis and how to start treating it.